Numerical Study of Supercritical Opposed Wall-Fired Boiler Furnace Temperature and High-Temperature Heating Surface Stress under Variable Load Operation - Jiajun Du; Yilong Li; Yonggang Zhao; Yaodong Da; Defu Che (Energies, 2024)
The opposed wall-fired boiler is widely used in Chinese power plants due to its adaptability. However, deviations from design conditions can cause the reduction of combustion efficiency and combustion stability, and the overheating of heating surfaces. This study conducted numerical simulations on a 600 MW supercritical opposed wall-fired boiler at 75%, 50%, and 30% Turbine Heat Acceptance (THA) load conditions. The variation of temperature field and heat flux in the furnace under different loads, and parameters such as distributions of heat flux, temperature, and the stress of the high-temperature heating surface are analyzed. Results indicate that reducing the load from 75% to 30% THA lowers the furnace outlet temperature from 1158 to 1009 K and reduces the average gas temperature of the high-temperature heating surface from 1800 to 1570 K. Under a high load, the maximum heat flux concentrates on the side water-cooled wall of the combustion zone. However, when the load decreases, the heat absorption shifts towards the main combustion zone. Furthermore, under a high load, the average wall temperature of the high-temperature heating surface remains at 1600 K with a uniform temperature distribution. In contrast, when the load drops to 30% THA, significant temperature differences appear on the heating surface, with a maximum difference of 400 K. This leads to excessive expansion and slagging on the high-temperature heating surface, particularly in the middle and lower sections, due to the increased stress. These findings offer valuable insights for optimizing the combustion characteristics of opposed wall-fired boilers and preventing overtemperature explosions on the platen heating surface.